Saw. - Poole, Ben (Auteur Publishing Central Books Limited [distributor], 2012)
Like all game changers within the horror genre, SAW was an independent success, a low-budget champion that flourished without the patronage of a big studio. Not bad for the most successful horror franchise ever, which has spawned subsidiary media and masses of merchandise, including a theme park rollercoaster ride. What is it about SAW that attracted such a following? In his contribution to the "Devil's Advocates" series, Ben Poole considers the SAW phenomenon from all aspects of film and media studies -- from its generic pedigree in both literature and film, to the visceral audience pleasures ("what would I do?") of the text, to the contrasting representations of men and women and the film's implicit criticism of masculinity.